(untitled) (Cadernos de Psicologia Social do Trabalho, 2011)
This paper reviewed and compared the theories of Louis Le Guillant and Christophe Dejours related to control over work and its impacts on worker's mental health. To do so, we used the researches these two authors had conducted among telephone operators in Paris. The main analysis category we have used to understand similitudes and differences between them was their base theory - marxism, to Le Guillant, and psychoanalysis, to Dejours. We could infer from our study that control over work has important impacts over telephone operators' mental health in both conceptions, but the role of organizational context and the centrality of control as a study field seems to differ, depending on the base theory used.